Bio-accumulation of Heavy Metals Present in Pulp and Paper Mill Effluents - Yeole, P.M.; Shrivastava, V.S. (Asian Journal of Chemistry, 2010)
Bio-accumulation of Ni, Cr, Mn, Zn, Cu, Fe and Cd present in pulp and paper mill effluents by Arachis hypogea (groundnut) and Lycopersicon esculentum (tomato) plants were investigated by performing pot experiment. The plants were treated with different concentrations of the metals in the form of their metal nitrates, through soil. In each case the investigation period was six weeks. The order of accumulation was Mn>Cu>Fe>Zn>Ni>Cr>Cd. The doses of the wastes were taken 25, 50, 75 and 100 mL, respectively. Throughout the experiment fresh samples of the waste were utilized. Also the concentrations of these metals in wastes and plant sample were determined by ICP-AES technique.